INTEGRATION OF PERSUASIVE COMMUNICATION AND ARTIFICIAL INTELLIGENCE FOR OPTIMIZING GLOBAL MARKET PENETRATION IN BIG BEE FARM AGRITOURISM, THAILAND - Mutoharoh Mutoharoh; Furtasan Ali Yusuf; Syadely Hanafi; Nuryati Nuryati; Dade Suparna; Anton Nasrullah; Endi Sutrisna; Marfuah Marfuah; Phillip G. Queroda (International Journal of Engagement and Empowerment (IJE2), 2026)
This study examines how the integration of persuasive communication and artificial intelligence (AI) in digital marketing can enhance the competitiveness of honey‑based agritourism micro, small, and medium enterprises (MSMEs), using Big Bee Farm in Thailand as a community‑service case. While previous work highlights the potential of AI‑driven marketing, few studies explicitly address how suggestive, story‑based communication strategies and human–technology collaboration shape MSME competitiveness in agritourism contexts, leaving a notable gap between technological adoption and strategic communication design. This study aimed to design and implement an integrated community‑service program that combined suggestive‑communication training, AI‑based digital marketing tools, and participatory mentoring to strengthen marketing capacity and global competitiveness. The activity employed a participatory, experiential‑learning design, involving farm managers, marketing staff, and tour guides, and applied qualitative and descriptive‑quantitative methods, including needs assessment, training modules, hands‑on AI workshops, mentoring, and pre‑post evaluations. The findings showed that participants improved their ability to craft persuasive, emotionally engaging messages, adopted AI tools for content generation, chatbot support, and market analysis, shifted from conventional to integrated, data‑driven promotion, and reported higher tourist engagement and sales potential. Theoretically, these results support a human‑centric perspective on digital transformation, where AI functions as an augmenting resource when aligned with strategic communication. Practically, the study provides a replicable model for community‑service programs seeking to strengthen MSME competitiveness through a holistic integration of technology, communication, and collaboration.